Kirk's general surgical operations - Novell, Richard; Baker, Daryll M.; Goddard, N.J; Kirk, R. M. (Raymond Maurice) (Churchill Livingstone/Elsevier, 2013)
Focuses on operative surgery. This title is aimed at a broad readership: the candidate preparing for the Intercollegiate FRCS in General Surgery or international equivalents; and the trained surgeon faced, through necessity, with undertaking an infrequently performed procedure.